Caching and Forwarding Mechanism for Smart Grid Communications Networks - Arif Faturrachman; Fakhri Rahmatullah; Sayid Huseini Elfarizi; Ratna Mayasari; Ridha Muldina Negara; Sri Astuti; Kharisma Bani Adam; Arif Indra Irawan (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
A smart grid aims to integrate alternative and renewable energy sources. NDN has the advantage of being better than IP networks and can optimize the delivery of information. The concept of Named Data Networking (NDN) is designed for smart grid systems. This study aims to implement the NDN concept on a smart grid system and analyze forwarding and caching strategies. The implementation of the system strategy is supported using the NDN network topology, which is based on IEEE 39. The author evaluates network performance by paying attention to parameters such as delay and cache hit ratio. From the data the author obtained, it can be concluded that the best route-LRU and client control-LRU systems are better choices to be implemented in a smart grid communication system than the best route-FIFO and client control-FIFO systems. In other words, the LRU caching override method is superior to the FIFO caching override method. Meanwhile, the forwarding method does not show significant graphical results. This happens because the forwarding method that the authors use has the same route determination. Something that differentiates between the best route and client control is only the control of selecting the path. The best route is controlled by the producer, and client control is controlled by the consumer.